Welding training for the community in Loa Janan Ilir District, Samarinda City - Samen Lolongan; Markus Tato Mangando; Ervan Ervan (Community Empowerment, 2022)
The majority of the people in Harapan Baru Village, Loa Janan Ilir Sub-district work as manual laborers, for example as bricklayers, market workers, and construction workers. In addition, employment opportunities are also limited in number. Therefore, this community service is intended to provide SMAW welding training in collaboration with the Loa Janan Ilir District Community Empowerment Institute. The method used is the lecture, question and answer, and welding practice. The materials given are SMAW welding machine operating procedures, SMAW welding components and various welding joints. The result is to provide insight into the material and practice of SMAW welding as a provision for entrepreneurship and work seeking.